Cardiac Emergencies in Children A Practical Approach to Diagnosis and Management (Springer International Publishing, 2018)
This book is primarily for pediatric and adult emergency room physicians, primary care providers, hospitalists, and nurses. It will also be useful for critical care specialists, cardiologists and trainees at all levels. Cardiac Emergencies in Children describes the pathophysiology of a diverse group of congenital and acquired heart conditions and presents a therapeutic rationale for treating children presenting with these conditions under life-threatening conditions. The book discusses the effects of surgery on hemodynamics and how to manage these effects. Also described are the daily challenges faced by physicians, including identifying a child with heart disease, interpreting chest radiographs, ECGs, and laboratory findings, and beginning appropriate therapies.